Pengaruh Bauran Pemasaran Jasa dan Motivasi terhadap Keputusan Bertransaksi di Bank Syari’ah di Kecamatan Seberang Ulu I Kota Palembang - Nadia Afrilliana; Dwi Rangga Yudha (P3M STIE Mulia Darma Pratama, 2020)
The purpose of this study was to determine the problem formulation whether there was the effect of service marketing mix and motivation on transaction decisions at Syari’ah banks in Seberang Ulu I District, Palembang City. The type of research used associative research, which was to determine the effect of service marketing mix and motivation on transaction decisions at Syari’ah Banks in Seberang Ulu I District, Palembang City. The variables were service marketing mix, motivation, transaction decisions. The sample in this study was 68 respondents, with purposive sampling technique as a sample. The data in this study were primary data, using a questionnaire method. The analysis technique was multiple linear regression obtained Y = 1,778 + 0,240X1 + 0,247X2. Simultaneously (Test F) there was a significant effect of service marketing mix and motivation on transaction decisions in Seberang Ulu I District, Palembang City. Partially (t test) that was the variable of service marketing mix that was tcount (2.283) > ttable (1.997). Motivation variable was tcount (2.937) > ttable (1.997).